The “Hidden Urbanization”: Trends of Impervious Surface in Low-Density Housing Developments and Resulting Impacts on the Water Balance - Strohbach, Michael W.; Döring, Anneke O.; Möck, Malte; Sedrez, Maycon; Mumm, Olaf; Schneider, Anne-Kathrin; Weber, Stephan; Schröder, Boris (Frontiers in Environmental Science, 2019)
Land consumption through expansive urbanization is a major obstacle towards sustainable development. In reaction, sustainability strategies and goals on national, supranational and global scale frequently include the target of slowing land consumption. The success of such strategies and goals is commonly measured with indicators that track the conversion of open space (e.g., forests and farmland) into built-up space. A process generally hidden from such indicators is the loss of pervious surface at the fine scale within residential areas, but evidence from case studies suggests that this process can be quite substantial. In this article, we studied this phenomenon from a slightly different angle by comparing the anticipated and actual impervious surface of residential areas. In order to do so, we compared development plans (i.e., the legally binding documents that steer building in Germany) with the actual implementation. We selected eight development plans of low-density (single-family) housing (PLAN), which were digitized along with the actual implementation visible on 2016 orthophotos (STATUS QUO). All sites but one showed a relative increase between 8 and 56% of impervious surface from PLAN to STATUS QUO. We then modelled the environmental impacts of these changes, using the local water balance as an illustrative example. For all sites with an increase of impervious cover, infiltration rates decreased by 4 to 19%, evaporation rates increased by 0.2 to 1% and surface runoff increased by 4 to 18%. The more impervious surface, the stronger the effect, but it also depended on soil type and modelled rain intensity. Our results point to a gap between planning and real-world outcomes and they underline the environmental consequences, illustrated by effects on the water balance. In order to prevent hidden urbanization, we suggest that more emphasis should be put on integrated sustainable design and monitoring of the real-world results.